RETRACTED: Synthesis and Properties of Novel Alkyl-Substituted Hexaazacyclophanes and Their Diradical Dications - Shunjie Li; Jian Chen (Molecules)
Radicals based on arylamine cyclophanes can be used as functional materials and show application potential in fields such as synthetic chemistry, molecular electronic components, organic light-emitting diodes, and catalytic chemistry. Using a Buchwald–Hartwig palladium-catalyzed aryl halide amination method, we synthesized a series of neutral hexaazacyclophane compounds 1–3 with different substituents in the meta–meta–meta positions of the phenyl rings. Three characteristic high-spin hexaazacyclophane diradical dications were obtained by two-electron oxidation using AgSbF6: 12·+•2[SbF6]−, 22·+•2[SbF6]−, and 32·+•2[SbF6]−. The electronic structures and physical properties of these compounds were then investigated by 1H and 13C nuclear magnetic resonance spectroscopy, cyclic voltammetry, electron paramagnetic resonance spectroscopy, superconducting quantum interferometry, ultraviolet–visible spectroscopy, and density functional theory calculations. The findings provide new ideas for designing radical species with novel physical properties and electronic structures. Importantly, the obtained radical species are not sensitive to air, making them valuable functional materials for practical applications.